Simulation of the economic impact of introducing rivaroxaban in a high-complexity hospital for venous thromboembolism prophylaxis - Diovanna Santos DE CARVALHO; Rafael Alves DE SOUZA; Andrea Cassia SFORSIN; Vanusa Barbosa PINTO; Maria Cleusa MARTINS; Cleber Esteves CHAVES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: this work aims to simulate the economic impact of the introduction of rivaroxaban for venous thromboembolism (VTE) prophylaxis, when compared to the therapeutic options used in the institution (unfractionated heparin and enoxaparin), in the period from January to February 2022. Methods: In a retrospective study, we analyzed the possibility of replacing the prophylaxis used in the institution with prophylaxis with rivaroxaban based on the analysis of data from the electronic medical record system, taking into account the length of stay, the medications prescribed and compliance with the institutional protocol. Patients prescribed medication for VTE prophylaxis and indicated according to progress in the medical record were included, excluding those using non-pharmacological prophylaxis. Patients with contraindications to the use of rivaroxaban, such as pregnancy and liver impairment, were also excluded. Monte Carlo Simulation was used to calculate the cost of treatment with DOACs (Direct Oral Anticoagulants), using the medicines acquisition values during the study period, and a decision tree was constructed. Results: A total of 157 patients who were prescribed one of the heparins were evaluated. Of these patients, 98 (62.4%) could undergo prophylaxis with rivaroxaban as they had no contraindication to this treatment (price recorded in January/February 2022: R$ 0.23). This new prophylaxis would generate savings of up to 98.4% for enoxaparin 40 mg (price recorded in January/February: R$ 14.26), the item that had the highest consumption, corresponding to 71.4% of patients who could use it rivaroxaban. Conclusion: The implementation of rivaroxaban for venous thromboembolism prophylaxis replacing enoxaparin proved to be beneficial in terms of costs for the hospital, which suggests that more studies should be carried out in order to increase the robustness of results and support the incorporation of this technology in the institution.